A history of American law - Friedman, Lawrence M. (Lawrence Meir), 1930- (New York, NY : Oxford University Press, 2019)
Renowned legal historian Lawrence Friedman presents an accessible and authoritative history of American law from the colonial era to the present day. This fully revised fourth edition incorporates the latest research to bring this classic work into the 21st century. In addition to looking closely at timely issues like race relations, the text covers the changing configurations of commercial law, criminal law, family law, and the law of property. Friedman furthermore interrogates the vicissitudes of the legal profession and legal education.
This edition also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 16, 2019).
Keywords: Law -- United States -- History